ANGUSTIFOLIA3 Binds to SWI/SNF Chromatin Remodeling Complexes to Regulate Transcription during Arabidopsis Leaf Development. Issue 1 (17th January 2014) - Vercruyssen, Liesbeth; Verkest, Aurine; Gonzalez, Nathalie; Heyndrickx, Ken S.; Eeckhout, Dominique; Han, Soon-Ki; Jégu, Teddy; Archacki, Rafal; Van Leene, Jelle; Andriankaja, Megan; De Bodt, Stefanie; Abeel, Thomas; et al.
Abstract : The transcriptional coactivator ANGUSTIFOLIA3 (AN3) stimulates cell division during Arabidopsis leaf development. It is shown that AN3 associates with SWI/SNF chromatin remodeling complexes to regulate the expression of important downstream transcription factors and that the module SWI/SNF-AN3 is a major player in the transition from cell division to cell expansion in developing leaves. Abstract: The transcriptional coactivator ANGUSTIFOLIA3 (AN3) stimulates cell proliferation during Arabidopsis thaliana leaf development, but the molecular mechanism is largely unknown. Here, we show that inducible nuclear localization of AN3 during initial leaf growth results in differential expression of important transcriptional regulators, including GROWTH REGULATING FACTORs ( GRFs ). Chromatin purification further revealed the presence of AN3 at the loci of GRF5, GRF6, CYTOKININ RESPONSE FACTOR2, CONSTANS-LIKE5 ( COL5 ), HECATE1 ( HEC1 ), and ARABIDOPSIS RESPONSE REGULATOR4 ( ARR4 ). Tandem affinity purification of protein complexes using AN3 as bait identified plant SWITCH/SUCROSE NONFERMENTING (SWI/SNF) chromatin remodeling complexes formed around the ATPases BRAHMA (BRM) or SPLAYED. Moreover, SWI/SNF ASSOCIATED PROTEIN 73B (SWP73B) is recruited by AN3 to the promoters of GRF5, GRF3, COL5, and ARR4, and both SWP73B and BRM occupy the HEC1 promoter. Furthermore, we show that AN3 and BRM genetically interact. The data indicate that AN3 associates with chromatin remodelers to regulate transcription. In addition, modification of SWI3C expression levels increases leaf size, underlining the importance of chromatin dynamics for growth regulation. Our results place the SWI/SNF-AN3 module as a major player at the transition from cell proliferation to cell differentiation in a developing leaf.